2011
DOI: 10.4137/bbi.s6061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drought-Responsive Universal Stress Proteins in Viridiplantae

Abstract: Genes encoding proteins that contain the universal stress protein (USP) domain are known to provide bacteria, archaea, fungi, protozoa, and plants with the ability to respond to a plethora of environmental stresses. Specifically in plants, drought tolerance is a desirable phenotype. However, limited focused and organized functional genomic datasets exist on drought-responsive plant USP genes to facilitate their characterization. The overall objective of the investigation was to identify diverse plant universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 56 publications
(113 reference statements)
3
49
0
1
Order By: Relevance
“…Besides, we have used USPA-like domains from Arabidopsis that are well-known for the presence of different protein kinase (PK) types (designated 1.3.1, 1.3.2, 1.4.1 or ''1MJH-like, plant'' in Kerk et al [7]) downstream the USPA domain. PK-like and/or protein tyrosine kinase-like (or tyr PK) sequences in putative USPAs of C. roseus exist downstream of the USPA-like domain [18]. U-Box domain is usually detectable at extreme C terminus of PK.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, we have used USPA-like domains from Arabidopsis that are well-known for the presence of different protein kinase (PK) types (designated 1.3.1, 1.3.2, 1.4.1 or ''1MJH-like, plant'' in Kerk et al [7]) downstream the USPA domain. PK-like and/or protein tyrosine kinase-like (or tyr PK) sequences in putative USPAs of C. roseus exist downstream of the USPA-like domain [18]. U-Box domain is usually detectable at extreme C terminus of PK.…”
Section: Resultsmentioning
confidence: 99%
“…Plant USP generally display an ATP-binding activity and also a signal transduction function [71]. In Arabidopsis, the cocoa homologous gene, At3g53990, was found to be up-regulated under drought conditions [72] and studies on cotton have shown that UPS genes can be up-regulated by gibberellic acid (GA) treatment [73]. GA is a phytohormone involved in plant development processes and cell elongation, [74].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The latter, USP family proteins, are also often expressed in many species under the unfavorable conditions, providing the organism with the ability to protect from various stresses and therefore this proteins constitute a useful target in stress tolerance engineering. Suggested function of the proteins containing USP domain is nucleotide binding and signal transduction (Nachin et al 2005;Isokpehi et al 2011). Its function under ABA conditions has not been studied yet.…”
Section: Stress Responsementioning
confidence: 99%